2021
DOI: 10.1177/10464964211060348
|View full text |Cite
|
Sign up to set email alerts
|

Translating Member Ability Into Group Brainstorming Performance: The Role of Collective Intelligence

Abstract: In investigating how member ability is translated into group brainstorming performance, it was predicted that a group’s collective intelligence (CI) would enable it to capitalize on member ability while maximizing process gains and mitigating process losses. Ninety-nine groups were randomly assigned to complete a short brainstorming task using a hybrid (individual-group work) or collective (only group work) task structure. High CI groups were better than low CI groups at translating member ability into group b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
(173 reference statements)
0
5
0
Order By: Relevance
“…Prominent definitions include "groups of individuals acting collectively in ways that seem intelligent" (Malone & Bernstein, 2015) and "the general ability of a group to perform a wide variety of tasks" (Woolley et al, 2010). More recently, researchers have identified different collective processes underlying collective intelligence, such as transactive memory, attention, and reasoning systems and skill congruence (Riedl et al, 2021) which provide groups the capability to better translate individual ability into collective performance (Ostrowski et al, 2022). Collective intelligence has been studied extensively in organizational science (Woolley et al, 2015;Malone et al, 2009;Massari et al, 2019), cognitive science (Galesic et al, 2019;Granovisky et al, 2015;Jayles et al 2020;Kurvers et al 2016), business (Bothos et al, 2012;Tauscher, 2017), managing intellectual capital (Secundo et al, 2016), and crisis management (Hernantes et al, 2013;Turoff et al, 2013), among other fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent definitions include "groups of individuals acting collectively in ways that seem intelligent" (Malone & Bernstein, 2015) and "the general ability of a group to perform a wide variety of tasks" (Woolley et al, 2010). More recently, researchers have identified different collective processes underlying collective intelligence, such as transactive memory, attention, and reasoning systems and skill congruence (Riedl et al, 2021) which provide groups the capability to better translate individual ability into collective performance (Ostrowski et al, 2022). Collective intelligence has been studied extensively in organizational science (Woolley et al, 2015;Malone et al, 2009;Massari et al, 2019), cognitive science (Galesic et al, 2019;Granovisky et al, 2015;Jayles et al 2020;Kurvers et al 2016), business (Bothos et al, 2012;Tauscher, 2017), managing intellectual capital (Secundo et al, 2016), and crisis management (Hernantes et al, 2013;Turoff et al, 2013), among other fields.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent definitions include ‘groups of individuals acting collectively in ways that seem intelligent’ [ 20 ] and ‘the general ability of a group to perform a wide variety of tasks' [ 12 ] . More recently, researchers have identified different collective processes underlying collective intelligence, such as transactive memory, attention, and reasoning systems [ 15 ] and skill congruence [ 21 ] which provide groups the capability to better translate individual ability into collective performance [ 22 ]. Collective intelligence has been studied extensively in organizational science [ 23 25 ], cognitive science [ 11 , 26 28 ], business [ 29 , 30 ], managing intellectual capital [ 31 ] and crisis management [ 32 , 33 ], among other fields.…”
Section: Introductionmentioning
confidence: 99%
“…EBS can be useful for enhancing the creativity of some students with high level of openness (Pi et al, 2022). Some researchers have proposed a hybrid structure (Ostrowski et al, 2022), constructive criticism (Curhan et al, 2021), or other innovative methods to overcome the weaknesses of brainstorming, such as strengthen the integration and application of innovation methods (Gallupe et al, 1991) and provide some structure to brainstorming sessions by asking a series of questions or requiring participants to engage in specific activities in order to make the sessions more productive (Gobble & Anne, 2014).…”
Section: Shortcomings Of Brainstorming Methodsmentioning
confidence: 99%
“…Initial research on these processes using collaborators’ self-report ratings demonstrated their value as significant predictors of team performance (Hackman & O’Connor, 2004; Wageman et al, 2005). More recent studies have identified digital traces of behavior to use in computational measures of collaborative-process behavior (Riedl et al, 2021) that correlate with observers’ ratings of collaboration and differentiate teams that are high versus low in CI (Glikson et al, 2019; Ostrowski et al, 2022; Woolley, Chow, et al, 2023; Zhao et al, 2023). When used as real-time diagnostic indicators of CI, these metrics enable interventions by human leaders or agent-based teammates, such as an agent-based facilitator that prompts discussion or digital “nudges” that draw collaborators’ attention to weak collaborative processes (Gupta et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the group could receive real-time feedback via visual displays to make contributors’ engagement more transparent in remote collaboration and encourage everyone to contribute when their effort is low (Glikson et al, 2019). These collaborative-process indicators can also help identify, a priori, which groups would benefit from proactive interventions to improve task strategy, such as using structured, hybrid brainstorming techniques to generate creative ideas (Ostrowski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%